Atlantic multidecadal variability and the implications for North European precipitation - Florian Börgel; H E Markus Meier; Matthias Gröger; Monika Rhein; Cyril Dutheil; Jan Moritz Kaiser (Environmental Research Letters, 2022)
The North Atlantic exhibits temperature variations on multidecadal time scales, summarized as the Atlantic multidecadal variability (AMV). The AMV plays an essential role for regional climate and is a key driver of the low-frequency variability in Northern Europe. This study analyzed the interaction between the atmosphere and the ocean using Coupled Model Intercomparison Project 6 (CMIP6) control runs. The results showed that the physical mechanisms underlying decadal or longer time scales differ among CMIP6 models, which allowed them to be sorted into two clusters. For the first cluster, a significant coherence between the North Atlantic Oscillation (NAO) and the AMV was found. Further, it showed a strong negative NAO response and decreasing precipitation over Northern Europe. In contrast, the second cluster showed no significant coherence between NAO and AMV. This non-coherent cluster developed a low-pressure anomaly in the subpolar gyre and showed increasing precipitation over Europe. Differences in the northward extension of the Atlantic meridional overturning circulation (AMOC) between the two clusters were identified and linked to the different atmospheric responses. Our findings have important implications for European climate, since predictions of an increase or decrease in precipitation over Northern Europe will be model-dependent.